2012
DOI: 10.1242/jeb.067124
|View full text |Cite
|
Sign up to set email alerts
|

Further insight into the sound-producing mechanism of clownfishes: what structure is involved in sound radiation?

Abstract: SUMMARYIt was recently demonstrated that clownfishes produce aggressive sounds by snapping their jaw teeth. To date, only the onset of the sound has been studied, which raises the question, what structure is involved in sound radiation? Here, a combination of different approaches has been used to determine the anatomical structure(s) responsible for the size-related variations observed in sound duration and frequency. Filling the swimbladder with physiological liquid specifically modified size-related acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Subsequent work indicated that damselfish sounds are initiated by a stretched ceratomandibular ligament that causes a rapid mouth closure and collision of front teeth [54]. Colleye et al then demonstrated that striking the ribs, which are intimately associated with the swimbladder, produces sounds with a similar frequency spectrum as sounds of the intact fish [55]. Thus, energy from teeth collisions is transferred to the ribs, and rib vibration drives the swimbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work indicated that damselfish sounds are initiated by a stretched ceratomandibular ligament that causes a rapid mouth closure and collision of front teeth [54]. Colleye et al then demonstrated that striking the ribs, which are intimately associated with the swimbladder, produces sounds with a similar frequency spectrum as sounds of the intact fish [55]. Thus, energy from teeth collisions is transferred to the ribs, and rib vibration drives the swimbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Sounds in pomacentrids are produced by a jaw slam that causes teeth collision [32,35,47]; for this reason the start of the sound corresponds to the bite. The sounds produced during fighting and during the biting of filamentous algae can be clearly recorded with a hydrophone.…”
Section: Electromyographymentioning
confidence: 99%
“…the slam of oral jaws). On the other hand, variation observed in pulse durations could be related to other aspects of sound production, such as sonic radiation (see [47]). In all sequences of grazing studied with high-speed video, the individuals keep their jaws closed to pull away algae.…”
Section: Sounds In Agonistic Behavior and Grazingmentioning
confidence: 99%
“…During simultaneous neurocranium elevation and hyoid depression, it acts as a cord, forcing rapid mouth closing [18] (figure 1). The forceful contact of the teeth of the upper and lower jaws is responsible for producing pulsed sounds [18,27]. As a result of the cmd ligament, the hyoid and mandible represent a coupled system that is subjected to, at least, two distinct functional demands: feeding and sound production.…”
Section: Introductionmentioning
confidence: 99%